Length-Weight Relationship and Condition Factor of the Bonga Shad Ethmalosa fimbriata (Bowdich, 1825) From the Escravos Estuary, Delta State, Nigeria - Eriegha, Ochuko Joshua; Eyo, Victor Oscar (Journal of Aquaculture and Fisheries, 2023)
Biometric data such as length-weight relationships and condition factor are veritable tools in fisheries management since it provide information about the growth of the fish, its general wellbeing, and fitness in an aquatic ecosystem. The length-weight relationship of Ethmalosa fimbriata collected from the Okerenkoko section of the Escravos estuary, Delta State, Nigeria was established, and its growth condition was evaluated using linear regression and Fulton’s condition factor equation respectively. The logarithmic transformation equation of the length-weight relationship for E. fimbriata is given by the equation: Log TW=3.0588Log TL–2.1759 (r2=0.9045, n=182, P<0.05). The computed b value (3.0588) was not significantly different (p>0.05) from 3 and revealed that fish growth is isometric. Condition factor (K) ranged between 0.620 for fish with total length (14.0 cm) and total weight (17.0 g) to 0.88 for fish with total length (16.3 cm) and total weight (38.0 g) with a mean and standard deviation value of 0.792 ± 0.01. The K value of this species in the Okerenkoko estuary indicated that they were not in good condition (K<1). The poor condition of the fish may be attributed to occasional crude oil spillage in the area. This is first baseline data about LWRs and condition factor of fish species from the Escravos estuary. This data is therefore valuable for establishing a monitoring and management system of this fish species.
Keywords: Escravos; Fish biometrics; Growth; Regression coefficients